A study on adopting international convention on oil pollution preparedness, response and co-operation, protocol for hazardous and noxious substances(oprc-hns) - Zakaria, Hasbullah (2001)
Since 30 October 1997, Malaysia has adopted the International Convention on Oil Pollution Preparedness and Response Co-operation (OPRC, 1990). The Convention was initially focused on oil pollution. In realizing the significance of hazardous and noxious substances to human and marine life, the International Maritime Organization (IMO) organized an International Convention on Preparedness and Response Co-operation on Pollution incidents arising from hazardous and noxious substances on 9-15 March 2000. Following the conference, a protocol has been developed under the convention and must be adopted by all the countries including Malaysia. Nevertheless prior to the adoption of this Convention by Malaysia a study concerning the benefit, implication and level of preparedness should be done. The outcome of the study shows that the Convention brings huge benefits to the country. Amongst the benefits or advantage to the country implementing the Convention indicates provisions ofa National Contingency Plan to control pollution on HNS at sea, a reporting system, and HNS spill equipment stockpile. Co-operation between countries implementing this Convention ensure that the parties are directly involved in handling HNS be it government agencies. Ports or industries have to allocate a budget for purchasing equipment and stockpile, prepare a contingency plan and training. While, Malaysia as one of the coastal states that has to adopted this Convention, it will not be implemented in the immediate future as the current capabi lities, interims of preparedness and other requirement are limited.